HUBUNGAN PENGASUHAN ANAK OLEH IBU DENGAN KEJADIAN DIARE PADA BALITA DI KELURAHAN SIRANDORUNG KECAMATAN RANTAU UTARA KABUPATEN LABUHANBATU - Sarah Mutia; Evawany Y Aritonang; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Nutrition is a process of organisms using food that is normally consumed through several processes to maintain the normal life, growth and function of the organs and generate energy. Consumption of good nutrition and enough is needed by someone, especially in children under five. Nutrition consumption will affect how the nutritional status of children under five. The fact that malnutrition is irreversible (can not recover). Malnutrition that occurs in this golden period can lead to infectious diseases that often occur in infants is diarrhea. The high incidence of diarrhea in infants is influenced by the lack of family knowledge, especially mothers in doing diarrhea treatment at home. This study was conducted to acknowledge the relationship between mother’s care pattern with the incident of diarrhea in children under fivein the Village of Sirandorung, North Rantau Sub District Labuhanbatu Regency. This study was an analytical descriptive research with cross sectional design. The data were obtained from direct interviews to mother covering the data of parenting (feeding, hygiene and environmental sanitation, and child care), and diarrhea incidence data. Data analysis was done univariat, bivariate, using chi-square test. The results of this study indicate good feeding care pattern of 55.7%, hygiene and environmental sanitation categorized both by 44.3% and good child care by 78.5%. Most infants had diarrhea in the last 3 months (67.1%). There is a relationship between mother's feeding pattern with the incidence of diarrhea in infants (p = 0.0001). There is a relationship between hygiene care pattern and environmental sanitation with the incidence of diarrhea in infants (p = 0.0001). And there is a relationship between child care with the incidence of diarrhea in infants (p = 0.036). Based on the results of the study is expected to improve counseling about good parenting patterns to under five and for health workers to motivate health cadres in disseminating information to mothers about parenting patterns in children underfive.